Survival rates of translocated Gunnison sage‐grouse. (14th March 2022) - Apa, Anthony D.; Gammonley, James H.; Neubaum, Daniel J.; Phillips, Evan; Runge, Jonathan P.; Seward, Nathan; Wait, Scott; Weinmeister, Brad
Abstract: Translocations have been used as a management tool for the federally threatened Gunnison sage‐grouse ( Centrocercus minimus ) but have not been rigorously evaluated. We estimated survival of translocated Gunnison sage‐grouse during the first year following release. Survival rates differed among satellite population where grouse were released, and survival was lower during the first 75 days following release than during the remainder of the first year. Age and sex of translocated grouse also influenced survival, but the timing of translocation (spring or fall) was less influential. Survival estimates of translocated Gunnison sage‐grouse were comparable to available estimates for resident Gunnison and greater sage‐grouse ( C. urophasianus ), suggesting that translocations may be an effective management tool for maintaining isolated populations. However, annual male counts at leks in the release populations were variable and generally declining, indicating that past numbers of Gunnison sage‐grouse translocated to these populations may not be adequate to sustain local populations, if lek counts reflect true population trends. Given that translocation has been identified as a primary management action for the recovery of Gunnison sage‐grouse, we recommend that a long‐term strategy for a translocation program should be developed. The success of a Gunnison sage‐grouse translocation program should be carefully monitored and managers should consider prioritizing captures for translocations with subadult females and males. Abstract : We estimated the post‐release survival of wild translocated Gunnison sage‐grouse ( Centrocercus minimus ) to 5 small isolated populations. Translocations can be an effective tool in species recovery, but a long‐term strategy for a translocation program should be developed and monitored.